Decomposing Terms of Trade Fluctuations in Ethiopia - Josef L. Loening; Masato Higashi (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper proposes a technique to decompose short-run fluctuations in the terms of trade. Using Ethiopia as an example, we decompose the commodity terms of trade into various components to measure the impact of price and volume shifts as well as export diversification. We use monthly data from the past decade, including periods during the global food and financial crises. Our findings suggest that diversification out of traditional coffee exports to other export commodities successfully mitigated a terms of trade shock. Continued export diversification will be beneficial.
Keywords: F14; O11; O55; 330; Terms of Trade; Food Price Crisis; Financial Crisis; Ethiopia; Terms of Trade; Volatilität; Exportdiversifizierung; Äthiopien; Finanzmarktkrise